2017
DOI: 10.5147/ajpb.v1i2.110
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure of Cactus Pear (Opuntia Ficus Indica) in Moroccan Collection

Abstract: Recently, a large plantation has been established in Morocco, to reduce water and wind erosion, rangeland degradation, sand movement and to enhance the restoration of the vegetation cover. However, this plant material has unknown genetic characterization. In addition, several local classifications and morphological descriptions were used. The objective of this study was to analyze the genetic diversity using RAPD markers in a collection of 13 provenances of Moroccan Opuntia ficus indica (L.). Based on 13 rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…It appears that the juice content of prickly pear fruit is dependent on the maturity of fruit, as well as the parts, season and region in which it was grown. These findings are consistent with the findings of El Finti et al (2013), who found that the weight of prickly pear fruits ranged between 81.5 and 107.5 g and the fruit pulp weight ranged between 47.98 and 63.44% in different varieties of prickly pear fruits. These show that the fruit pulp weight is directly related to the weight of the entire fruit.…”
Section: Physical Properties 311 Weight Of Fruit and Its Fractionssupporting
confidence: 92%
See 1 more Smart Citation
“…It appears that the juice content of prickly pear fruit is dependent on the maturity of fruit, as well as the parts, season and region in which it was grown. These findings are consistent with the findings of El Finti et al (2013), who found that the weight of prickly pear fruits ranged between 81.5 and 107.5 g and the fruit pulp weight ranged between 47.98 and 63.44% in different varieties of prickly pear fruits. These show that the fruit pulp weight is directly related to the weight of the entire fruit.…”
Section: Physical Properties 311 Weight Of Fruit and Its Fractionssupporting
confidence: 92%
“…They found that the TSS was 14.47, 13.02, and 14.45 °brix in orange, purple, and green prickly pear fruit from South Africa. It is also lower than the results found by El Finti et al (2013) in Moroccan prickly pear fruits (17.03-19.75) °brix; Abdulkadir et al (2022) in red cactus pear from the Eastern Tigray region, north Ethiopia (13.95) °brix; Reis et al (2018) in cactus pears from Portugal (13.05-15.63%); and Gómez-Maqueo et al (2020) in prickly pear fruit pulp from the Canary Islands (13.4-16) °brix. Despite the lower numbers found in our study, it is clear that there has been a steady improvement over time in the total soluble solid content of prickly pear fruit.…”
Section: Total Soluble Solidsmentioning
confidence: 55%
“…Cherratia, Angad, Melk Zhar, Belara, and Marjana have fruits with large sizes (134.5-276.7 g) that exceed 120 g destined for export (Inglese et al, 1995a). The fruit weight values recorded for the resistant Opuntia cactus varieties studied in this work are relatively higher than the values of El Finti et al (2013) who found weights between 80.6 g and 106.5 g for 13 cultivars from different regions of Morocco; very higher than the values found by El Kharrassi et al (2016), who found fruit weights ranging from 53 g to 103 g after evaluation of 30 accessions from different regions in Morocco. Mulas et al (2006) who worked on 20 accessions of wild Opuntia in Morocco also found values ranging from 41.7 g to 92.2 g. The weight and size of cactus fruits are highly influenced by environmental conditions and cultivation methods.…”
Section: Discussionmentioning
confidence: 56%
“…in Phoenix dactylifera L. 35 , Olea europaea L. 8 , Citrus sinensis to assess the genetic variability within 36 Tunisian accessions, and a considerable genetic diversity was detected. In Morocco, the genetic diversity within O. ficus indica accessions was evaluated using RAPD markers 18 , and the effect of the geographical origin was revealed. In our case, findings showed high genetic similarity among the studied accessions of O. ficus indica, even though they were collected from different regions of Morocco.…”
Section: Discussionmentioning
confidence: 99%
“…The accessions of this species are classified into three distinct populations: (i) the Christians' nopal with prickly cladodes used as a field fence; (ii) the Muslims' nopal with inermis cladodes used as a green fodder for cattle and (iii) the Moses' nopal with large inermis cladodes that produce big pears 20 . The cactus pear population is present throughout the country, from Eastern to Southern Morocco 18 , with predominance in Guelmim-Sidi Ifni and Haouz-El Kelâa des Sraghnas regions 5 . Increasing the cactus pear area of cultivation is one of the strategies of the Moroccan Ministry of Agriculture.…”
Section: Introductionmentioning
confidence: 99%